2013
DOI: 10.4097/kjae.2013.65.4.317
|View full text |Cite|
|
Sign up to set email alerts
|

Heart rate variability as a predictor of hypotension after spinal anesthesia in hypertensive patients

Abstract: BackgroundHypotension is a common phenomenon after spinal anesthesia in hypertensive patients. We investigated whether heart rate variability could predict the occurrence of hypotension after spinal anesthesia in hypertensive patients.MethodsForty-one patients undergoing spinal anesthesia were included. Heart rate variability was measured at five different time points such as before fluid loading (baseline), after fluid loading as well as 5 min, 15 min and 30 min after spinal anesthesia. Fluid loading was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
1
19
0
2
Order By: Relevance
“…In contrast to the previous studies [7][8][9][10][11][12] focused on the detection of influence of different anesthetic drugs on autonomic control of heart rate and arterial pressure, the present study was aimed at estimating the strength and direction of coupling between the autonomic control of heart rate and vascular tone for the patients under the spinal block and the ataractanalgesia. In [8][9][10] it was demonstrated that propofol suppresses the activity of sympathetic control of heart rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previous studies [7][8][9][10][11][12] focused on the detection of influence of different anesthetic drugs on autonomic control of heart rate and arterial pressure, the present study was aimed at estimating the strength and direction of coupling between the autonomic control of heart rate and vascular tone for the patients under the spinal block and the ataractanalgesia. In [8][9][10] it was demonstrated that propofol suppresses the activity of sympathetic control of heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier it was demonstrated in [7][8][9][10][11][12] that different anesthetic drugs have different impacts on sympathetic and parasympathetic control of heart rate and arterial pressure. During the choice of a therapy it is important to take into account the patient's circulation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Terjadi dilatasi pada vena dan venule perifer dengan pengumpulan darah akan menurunkan curah balik ke jantung sehingga akan menyebabkan penurunan curah jantung dan tekanan darah. 18,19 Semakin banyak daerah yang mengalami denervasi simpatis seperti pada bupivakain hiperbarik maka akan semakin banyak arteri dan vena yang mengalami dilatasi sehingga memperbesar persentase penurunan tekanan darah yang lebih tinggi dibandingkan dengan bupivakain isobarik. 20,21 Hal ini memperlihatkan perbedaan luas area yang terkena blokade pada kedua kelompok akan memberi efek pada tekanan darah yang secara teori dijelaskan bahwa semakin luas daerah blokade maka akan terjadi penurunan resistensi pembuluh darah sistemik sehingga penumpukan darah pada vena semakin besar, pada akhirnya akan menurunkan aliran darah yang kembali ke jantung.…”
Section: Volume 11 Nomor 3 Tahun 2019unclassified
“…A través de un método no invasivo que mide y analiza la variabilidad de la frecuencia cardíaca 12 ; varios estudios han demostrado el valor predictivo de este en maternas programadas para cesárea 13,14 ; sin embargo, queda determinar su aplicabilidad en población no obstétrica 7 . El análisis se realiza bajo los estándares del Task Force 15 , consiste en un registro de 5 minutos de ondas R rápidas en electrocardiograma a una frecuencia de 1024 Hz; se calcula un espectro de densidades para frecuencias bajas y para frecuencias altas, LF y HF por sus siglas en inglés, respectivamente 7,16 . Se ha propuesto que la relación LF/HF refleja el balance de la regulación del sistema nervioso autónomo es decir, la relación entre los componentes simpático y parasimpático 13 , siendo LF la actividad vasomotora (como índice indirecto de actividad simpática) y HF la actividad vagal [17][18][19][20] .…”
Section: Fisiopatologia Y Factores De Riesgounclassified